RIGHT VENTRICULAR INFARCTION IN PATIENTS WITH INFERIOR WALL MYOCARDIAL INFARCTION AND THEIR CLINICAL AND ANGIOGRAPHIC PROFILE AND OUTCOMES (The Research of Medical Science Review, 2025)
OBJECTIVE To determine the frequency of right ventricular infarction (RVI) in patients presenting with inferior wall myocardial infarction (IWMI) and to analyze their clinical presentation, angiographic profile, and in-hospital outcomes to help with early diagnosis and management. METHODOLOGY This descriptive study was done during the year 2024 at NICVD Karachi and included patients aged between 18 to 65 years who were present with IWMI and underwent PCI. Diagnosis of IWMI was made if the ECG revealed ST segment elevation in inferior leads (II, III, and AVF) with reciprocal ST segment depression in lateral or high lateral leads (I, AVL, V5 and V6). Right ventricular infarction (RVI) was labeled if ECG demonstrated ST elevation in V1, ST elevation in V1 with ST depression in V2, an isoelectric ST segment in V1 with marked ST depression in V2, or ST elevation in lead III greater than lead II, and was confirmed by ST elevation in right-sided leads (V3R–V6R). The data was entered analyzed through SPSS version 26. RESULTS The mean age of the participants was found to be 57.31with (SD = 6.21) years, and 66.5% of them were over 55 years old. The study had a male predominance, which represented 60.7% of the participants. Infarction of right ventricle (RVI) developed in 44.5% of cases. Infected patients with RVI had increased hypotension (18.8% vs. 4.8%, p=0.035), arrhythmia (12.9% vs. 5.8%, p=0.041), cardiac arrest (10.6% vs. 2.8%, p=0.029), atrioventricular block (11.8% vs. 4.0%, p=0.034), cardiac failure (8.2% vs. 2.1%, p=0.040), single-vessel disease (4.7% vs. 5.7%), double-vessel (29.4% vs. 31.1%) and triple-vessel (65.9% vs. 63.2%) with in significant difference (p=0.914) and mortality (12.9% vs. 3.1%, p=0.003). CONCLUSION This study reported the clinical impact of right ventricular infarction (RVI) in patients with inferior wall myocardial infarction (IWMI). Patients with RVI had a higher incidence of hypotension, arrhythmias, cardiac arrest, AV block, and in hospital mortality, compared with patients without RVI. Despite insignificant difference in types of CAD between groups these findings emphasis on early diagnosis by right-sided ECG and echocardiography as well as the need for standardization of treatment protocols to improve clinical outcome.